Mathematical Semiotics in Primary Learning: Helping Prospective Teachers Understand Mathematical Representations - Purwasih, Ratni; Irawan, Edi; Minasyan, Sona (Universitas Muhammadiyah Mataram, 2025)
Mathematics learning in elementary schools is often faced with the challenge of bridging abstract concepts with participants' concrete experiences. One of the reasons is the difficulty in understanding and using mathematical signs and symbols appropriately. Semiotic representation of mathematics, which involves symbols, diagrams and notations as visual and conceptual aids, is an important approach in overcoming these challenges. This study aims to explore the ability of prospective elementary school teachers to understand and use semiotic representations of mathematics, especially in the context of number patterns. A qualitative approach with a hermeneutic phenomenological design was chosen to understand prospective teachers' experiences, views, and thought processes in interpreting and using mathematical symbols. The researcher used written tests and semi-structured interviews as data collection techniques to explore the semiotic representations used in mathematical problem solving. The participants were grouped based on the results of the initial ability test, and six of them were selected as research subjects. Data analysis used the Interpretive Phenomenology Analysis (IPA) method with the help of NVivo 14 Plus software, which allows researchers to systematically manage and analyze qualitative data. The results of this study are expected to provide insight into prospective teachers' understanding of symbolic representation in mathematics learning and the challenges they face, which can be the basis for designing more effective learning strategies in the context of mathematics education in primary schools. Using a descriptive qualitative approach, data were obtained through observation and analysis of problem solving activities involving symbolic and visual representations. The results of the study are expected to provide insight into the importance of semiotic training in prospective teacher education, so that they are able to convey mathematical concepts meaningfully and contextually.